Visceral Hypersensitivity and Altered Colonic Motility in Type 2 Diabetic Rat - Sung, Tae Sik (J Neurogastroenterol Motil, 2015)
BACKGROUND/AIMS: Abnormal visceral sensitivity and disordered motility are common in patients with diabetes mellitus. The purpose of the present study was to investigate whether visceral sensation and bowel motility were altered in a rat model of type 2 diabetes mellitus accompanied by weight loss. METHODS: A type 2 diabetic rat model in adulthood was developed by administrating streptozotocin (STZ; 90 mg/kg, i.p.) to neonatal rats. Eight weeks after STZ administration, rats with blood glucose level of 200 mg/dL or higher were selected and used as diabetic group (n = 35) in this study. Abdominal withdrawal reflex and arterial pulse rate were measured to examine visceral nociception induced by colorectal distension (0.1–1.0 mL). The amplitude, frequency, and area under the curve (AUC) of spontaneous phasic contractions of colonic circular muscles were recorded in vitro to examine colonic motility. RESULTS: STZ-treated diabetic rats gained significantly less weight for 8 weeks than control (P < 0.01). Forty-eight percent of the diabetic rats showed enhanced visceral nociceptive response to colorectal distension. Diabetic rats did not differ from control rats in colorectal compliance. However, the frequency and AUC, not the amplitude, of colonic spontaneous contraction in vitro was significantly decreased in diabetic rats compared to control rats (P < 0.01 in frequency and P < 0.05 in AUC). CONCLUSIONS: These results demonstrate visceral hypersensitivity and colonic dysmotility in a rat model of type 2 diabetes mellitus accompanied by weight loss.